Comparison with and without P12 Nutraceutical Supplementation in Feed on Egg Productivity and Quality of Laying Hens - Heratri, Agnes; Putra, Arief Sobryan Esa; Tugiyanti, Elly (Jurnal Agripet, 2025)
The egg production and quality are crucial indicators in the layer chicken industry. Optimal productivity in layer chicken farming requires the use of nutraceutical-based feed comprising probiotics, herbs, amino acids, and vitamin A. This study aims to assess the effects of nutraceutical feed on two primary parameters: productivity and egg quality. The study was carried out over four weeks at the Peternakan Rakyat Tepus in Mojogedang, Karanganyar with a chicken population of 1.206. This study was a designed in a Completely Randomized Design (CRD) with two treatments: feed without supplementation (T0) and feed with supplement contains probiotics, herbs, amino acids, and vitamin. The study findings indicated that adding the nutraceuticals PR12 at 4 kg/ton in the feed did not exhibit a significant difference (P0.05) in daily feed consumption. However, feed conversion ratio (FCR), hen day production (HDP), egg weight, egg mass, yolk index, and Haugh unit were significantly different (P0.05). The incorporation of nutraceuticals (PR12) into the feed can enhance HDP, egg weight, and egg mass, and improve FCR. In conclusion, adding PR12 nutraceuticals, composting of probiotics, herbs, amino acids, and vitamin A at a dosage of 4 kg/ton in the feed can enhance the productivity of laying hens by 16.39%, resulting in eggs classified within the AA quality category.